Fiscal Policy and Government Revenue Nexus: Evidence from Nigeria - Okoh, Johnson I.; Oludami, Afrogha Olufolakemi; Agbadua, Oyakhiromhe Bamidele; Amahi, Fidelis U.; Oyeranmi, Akinloye O. (The Journal of Accounting and Management, 2023)
This paper examined the nexus of fiscal policy and government revenue in Nigeria over a period of 41years. The study made use of secondary data garnered from the Central bank of Nigeria Statistical bulletin for the period covered. The requisite diagnostic tests were conducted on the time series data to ensure that the data was fit for empirical use. The study employed the Ordinary Least Squares Regression (OLS) method. The method was adjudged appropriate for the study because of the Best Linear Unbiased Estimator property (BLUE) of the OLS. The estimation result revealed that all the independent variables except Government Domestic Debt (GDOD) were positively correlated with the dependent variable. It was further reveals that all the independent variables except Government Capital Expenditure are empirically significant to Total Federally Collected Revenue in Nigeria. From, the F-statistic, the study concluded that fiscal policy has strong statistical influence on government revenue in Nigeria.